A new microfluidic platform for the highly reproducible preparation of non-viral gene delivery complexes. Issue 1 (8th December 2022) - Protopapa, Giovanni; Bono, Nina; Visone, Roberta; D'Alessandro, Fabio; Rasponi, Marco; Candiani, Gabriele
Abstract : We describe the design and development of a new stand-alone microfluidic cartridge for the fast and repeatable preparation of non-viral gene delivery complexes at different N/Ps and their storage. Abstract : Transfection describes the delivery of exogenous nucleic acids (NAs) to cells utilizing non-viral means. In the last few decades, scientists have been doing their utmost to design ever more effective transfection reagents. These are eventually mixed with NAs to give rise to gene delivery complexes, which must undergo characterization, testing, and further refinement through the sequential reiteration of these steps. Unfortunately, although microfluidics offers distinct advantages over the canonical approaches to preparing particles, the systems available do not address the most frequent and practical quest for the simultaneous generation of multiple polymer-to-NA ratios (N/Ps). Herein, we developed a user-friendly microfluidic cartridge to repeatably prepare non-viral gene delivery particles and screen across a range of seven N/Ps at once or significant volumes of polyplexes at a given N/P. The microchip is equipped with a chaotic serial dilution generator for the automatic linear dilution of the polymer to the downstream area, which encompasses the NA divider to dispense equal amounts of DNA to the mixing area, enabling the formation of particles at seven N/Ps eventually collected in individual built-in tanks. This is the first example of a stand-alone microfluidic cartridge for the fast and repeatable preparation of non-viral gene delivery complexes at different N/Ps and their storage.